(untitled) (GRESIA, 2025)
As part of the learning process of students, formative research is a key factor to strengthen competencies in future professionals. For this reason, the following article presents abstracts of the experimental proyects carried out in the Environmental Biotechnology course of the Environmental Engineering program at the Universidad Antonio Nariño. Its main objective was the isolation of microorganisms with biotechnological potential: in this case, students focused mainly on biofuels and bioremediation.